A three-dimensional mathematical model to predict air-cooling flow and temperature distribution of wire loops in the Stelmor air-cooling system. (April 2017) - Hong, Lingxiang; Wang, Bo; Feng, Shuai; Yang, Zhiliang; Yu, Yaowei; Peng, Wangjun; Zhang, Jieyu
Highlights: A 3-dimentioanl mathematical models for complex wire loops was set up in Stelmor. The air flow field in the cooling process was simulated. The convective heat transfer coefficient was simulated coupled with air flow field. The temperature distribution with distances was predicted. Abstract: Controlling the forced air cooling conditions in the Stelmor conveyor line is important for improving the microstructure and mechanical properties of steel wire rods. A three-dimensional mathematical model incorporating the turbulent flow of the cooling air and heat transfer of the wire rods was developed to predict the cooling process in the Stelmor air-cooling line of wire rolling mills. The distribution of cooling air from the plenum chamber and the forced convective heat transfer coefficient for the wire loops were simulated at the different locations over the conveyor. The temperature profiles and cooling curves of the wire loops in Stelmor conveyor lines were also calculated by considering the convective heat transfer, radiative heat transfer as well as the latent heat during transformation. The calculated temperature results using this model agreed well with the available measured results in the industrial tests. Thus, it was demonstrated that this model can be useful for studying the air-cooling process and predicting the temperature profile and microstructure evolution of the wire rods.